2021
DOI: 10.1111/ajae.12245
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence on Adoption and Impact of the System of Rice Intensification

Abstract: We report the results of a large-scale, multi-year experimental evaluation of the System of Rice Intensification (SRI), an innovation that first emerged in Madagascar in the 1980s and has now diffused to more than 50 countries. Using a randomized training saturation design, we find that greater cross-sectional or intertemporal intensity of direct or indirect training exposure to SRI has a sizable, positive effect on Bangladeshi farmers' propensity to adopt (and not to disadopt) SRI. We find large, positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…The parameter also indicates that adopting SRI in rice cultivation could increase the rice yield of farm households by about 15.1%. This result is in line with the studies of Varma (2019), Kadigi et al (2020), Mishra et al (2021), and Barrett et al (2022), who found that SRI adoption could increase rice yields through an estimated econometric model.…”
Section: The Impact Of Sri Adoption On Rice Yieldssupporting
confidence: 92%
See 1 more Smart Citation
“…The parameter also indicates that adopting SRI in rice cultivation could increase the rice yield of farm households by about 15.1%. This result is in line with the studies of Varma (2019), Kadigi et al (2020), Mishra et al (2021), and Barrett et al (2022), who found that SRI adoption could increase rice yields through an estimated econometric model.…”
Section: The Impact Of Sri Adoption On Rice Yieldssupporting
confidence: 92%
“…Increasing agricultural productivity, particularly rice productivity, is essential to achieve food security and enhance household income, especially in low and middle-low-income countries, where many farmers rely on rice cultivation. A new technique for paddy production -the System of Rice Intensification (SRI) -has recently attracted interest and been widely introduced in many countries, with support from Africare, the Oxford Committee for Famine Relief (OXFAM), the World Wildlife Fund (WWF), and World Bank (Barrett, Islam, Mohammad Malek, Pakrashi, & Ruthbah, 2022). The SRI practice, developed by Father Laulanié in Madagascar in the mid-1980s, is an approach to…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest field experiments has been conducted in Bangladesh, where more than 180 villages and 5,000 farmers are involved. The allocation of training of SRI was first randomized at the village level and then at the household level within a treated village (Barrett et al 2021). Training intensification, in terms of the number of trainings conducted and the proportion of farmers eligible to participate in training, is intentionally varied between villages in order to investigate the heterogeneous impact of training.…”
Section: Impacts In Irrigated Conditionsmentioning
confidence: 99%
“…In this connection, it must be acknowledged that recent randomised controlled trials have the strong potential to provide causal evidence of some of SRI's benefits (e.g. Barrett et al 2022). However, it is also crucial to understand the extent to which the SRI uptake is affected by a province's institutional and infrastructural setup, and whether aggregate policy conclusions can be derived regarding SRI's benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Barrett et al . 2022). However, it is also crucial to understand the extent to which the SRI uptake is affected by a province's institutional and infrastructural setup, and whether aggregate policy conclusions can be derived regarding SRI's benefits.…”
Section: Introductionmentioning
confidence: 99%